Generative AI in education: To embrace it or not? - Okaiyeto, Samuel Ariyo; Bai, Junwen; Xiao, Hongwei (International Journal of Agricultural and Biological Engineering, 2023)
Generative Artificial Intelligence (AI) has gained immense popularity, but it has also brought forth new challenges and concerns in academia. One major worry is AI-assisted cheating, where students use Generative AI to complete assignments and exams, leading to some U.S. schools banning its usage on campus. However, the developers of ChatGPT, OpenAI, assured the public that they never intended ChatGPT to be used deceitfully in schools or elsewhere. They are already working on mitigations to make it easier for anyone to recognize text produced by that system. Open AI went ahead to state that they were looking forward to working with educators on practical solutions, and other ways to help teachers and students benefit from AI. DOI: 10.25165/j.ijabe.20231603.8486Citation: Okaiyeto S A, Bai J W, Xiao H W. Generative AI in education: To embrace it or not? Int J Agric & Biol Eng, 2023; 16(3): 285–286.